2021
DOI: 10.1029/2021ea001669
|View full text |Cite
|
Sign up to set email alerts
|

Forward Modeling of the Phobos Tides and Applications to the First Martian Year of the InSight Mission

Abstract: The tidal response of Mars, due to the Sun and the Martian moons, Phobos and Deimos, provides information about the interior structure of Mars. By using the VBB seismometer of SEIS as a gravimeter on the surface of Mars, the InSight mission will provide long-period data suited to tidal analysis: most notably, the proximity of Phobos implies that degree 2, 3, 4 and further tides will be detectable by the VBB and are expected to provide information about the rheology at different depths within Mars. In order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 70 publications
(258 reference statements)
0
1
0
Order By: Relevance
“…Future work will improve interior models, search for hidden seismic or infrasound events (Garcia et al 2021, Ortiz et al 2022, particularly with machine learning (Dahmen et al, 2022, Stott et al, 2022 and search for phases or long period signals not yet confirmed, including PKP phases (Irving et al 2022), surface wave overtones (Xu et al 2020), normal modes (Lognonné et al 2022) and tides (Pou et al 2021). As has been seen for the Apollo Lunar Surface Experiment (Bates et al 1979), we can expect decades of scientific analysis with SEIS and InSight data.…”
Section: Discussionmentioning
confidence: 99%
“…Future work will improve interior models, search for hidden seismic or infrasound events (Garcia et al 2021, Ortiz et al 2022, particularly with machine learning (Dahmen et al, 2022, Stott et al, 2022 and search for phases or long period signals not yet confirmed, including PKP phases (Irving et al 2022), surface wave overtones (Xu et al 2020), normal modes (Lognonné et al 2022) and tides (Pou et al 2021). As has been seen for the Apollo Lunar Surface Experiment (Bates et al 1979), we can expect decades of scientific analysis with SEIS and InSight data.…”
Section: Discussionmentioning
confidence: 99%